Nivel de cultura tributaria y conocimientos financieros de los trabajadores de la zona registral N° IV - sede Iquitos, 2021 - Macedo Bardales, Ingrid Julexsy (2022)
The present research work entitled "Level of Tax Culture and Financial Knowledge of the Workers of the Registration Zone No. IV - Iquitos Headquarters, 2021", was carried out with the objective of determining what is the level of Tax Culture and Financial Knowledge of the Workers of the Registration Zone IV Headquarters - Iquitos, 2021. For this, the type of descriptive research and Non-Experimental research design was used, 71 workers of the Registration Zone No. IV - Iquitos Headquarters were taken into account as a study population, to whom a survey was applied with the data collection instrument called a questionnaire; the work concluded that on average the workers have a low level of tax culture according to the results obtained; Regarding the level of tax culture, 33.8% had a high level of tax culture, 21.1% had a medium level and 45.1% had a low level, in terms of financial knowledge, 62% refer to a high level of financial knowledge, 12.6% refer to a medium level, and 25.4% refer to a low level, for which it was determined that the level of tax culture of the workers of the Registration Zone No. IV – Iquitos headquarters, 2021, is low and the level of financial knowledge is high.